Zakat as a Legal Obligation in Sharia within the Context of Contemporary Taxation Systems - Alwy Ahmed Mohamed; Abdulrohim E-sor (Demak Universal Journal of Islam and Sharia, 2025)
Objective: This study aims to investigate the feasibility and implications of integrating Zakat, an Islamic obligatory almsgiving system, into modern state taxation structures within Muslim-majority countries. Theoretical framework: The research is grounded in two complementary theoretical frameworks: fiscal sociology, which explores how taxation reflects socio-legal norms, and Islamic economic theory, which emphasizes wealth redistribution through moral and religious obligations.  Literature review: The literature review highlights that while scholars such as Yusuf al-Qaradawi, Monzer Kahf, and Habib Ahmed have extensively discussed zakat’s socio-economic role, there remains a gap in practical models that link zakat to national tax regimes without compromising Sharia principles or state fiscal efficiency. The coexistence of these systems often leads to conceptual confusion and administrative inefficiencies, particularly in countries like Malaysia, Indonesia, Pakistan, and Saudi Arabia. Methods: Methodologically, this research adopts a qualitative, comparative legal and economic approach, drawing on policy documents, legal statutes, and case studies from selected Muslim-majority countries. It critically examines institutional frameworks, public finance policies, and compliance behavior, while also employing doctrinal analysis of maqāṣid al-sharīʿah (objectives of Islamic law) to assess religious alignment. Results: The findings reveal that integration is hampered by legal fragmentation, institutional redundancy, and low public trust. However, models that incorporate zakat into the tax system—either through deductions, exemptions, or parallel recognition—demonstrate improved compliance, reduced welfare burdens on the state, and enhanced civic participation rooted in religious ethics. The study proposes a Hybrid Integration Framework comprising legal recognition, digital registries, transparent oversight, taxpayer choice mechanisms, and intersectoral collaboration. Implications: The implications of this research are significant for policymakers seeking to harmonize Sharia-based obligations with secular governance systems. By fostering synergy between religious mandates and public finance tools, this study offers a pathway toward more equitable and accountable fiscal models. Novelty: The novelty of this study lies in its dual-theoretical lens and the practical policy framework it develops for integrating religious and civic financial duties in a way that aligns with both ethical and administrative imperatives.